2017
DOI: 10.1111/ene.13304
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of STIM1/Orai1 in platelets of stroke patients predictive of poor outcomes

Abstract: A high expression level of platelet Orai1/STIMI1 was associated with poor clinical outcome (mortality and recurrence) and functional recovery (SIS scores) during the 3-month follow-up. Thus, we propose that these proteins are strongly predictive of life quality in patients with IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This was first described in the setting of (experimental) stroke, where platelets and T cells drive secondary thrombo-inflammatory brain infarct growth despite successful recanalization of the previously occluded brain artery. Recent experimental data has highlighted a critical role of the platelet GPVI/LAT/PLCγ2/STIM1/Orai1 axis in this process (9, 10, 43), and increased expression levels of STIM1/Orai1 have been proposed to serve as a predictor for poor outcome of stroke (44). To assess the pathophysiological significance of BIN2-dependent SOCE in this process, we subjected Bin2 fl/fl,Pf4-Cre mice to the transient middle cerebral artery occlusion (tMCAO) model of ischemic stroke, in which the middle cerebral artery (MCA) was transiently occluded by insertion of a filament as described previously (45).…”
Section: Stim1 Interacts With Bin2 In Plateletsmentioning
confidence: 99%
“…This was first described in the setting of (experimental) stroke, where platelets and T cells drive secondary thrombo-inflammatory brain infarct growth despite successful recanalization of the previously occluded brain artery. Recent experimental data has highlighted a critical role of the platelet GPVI/LAT/PLCγ2/STIM1/Orai1 axis in this process (9, 10, 43), and increased expression levels of STIM1/Orai1 have been proposed to serve as a predictor for poor outcome of stroke (44). To assess the pathophysiological significance of BIN2-dependent SOCE in this process, we subjected Bin2 fl/fl,Pf4-Cre mice to the transient middle cerebral artery occlusion (tMCAO) model of ischemic stroke, in which the middle cerebral artery (MCA) was transiently occluded by insertion of a filament as described previously (45).…”
Section: Stim1 Interacts With Bin2 In Plateletsmentioning
confidence: 99%
“…This process offers protectionto mice from ischemic stroke [61]. Dong M et al reported that STIM1/Orai1 expression was associated with mortality and recurrence in ischemic stroke patients and was an independent predictor of the 3-month stroke recovery [62].…”
Section: Discussionmentioning
confidence: 99%
“…Several potential mechanisms consist of endothelial dysfunction, [24] oxidative stress, [25] activation of inflammation, [26] proliferation of smooth-muscle, increased adhesion of monocytes to endothelial cells [27] and platelet dysfunction. [28,29]…”
Section: Discussionmentioning
confidence: 99%